Critical illness polyneuropathy: clinical findings and outcomes of a frequent cause of neuromuscular weaning failure - Hund, Ernst; Fogel, Wolfgang; Krieger, Derk; Hacke, Werner; DeGeorgia, Michael (Critical care medicine, 1996)
Detailed electrodiagnostic studies were done in all patients 3 to 6 wks (median 4.5) after the onset of the acute illness and were repeated 3 months to 3.5 yrs later in those patients who survived. Primary illnesses included various intracranial and medical conditions. All patients had moderate-to-severe limb weakness with marked muscle atrophy. Tendon reflexes were decreased in three patients, exaggerated in two patients with intracranial lesions, and absent in two patients. Electromyography demonstrated severe acute denervation, with striking involvement of proximal muscles. Muscle and nerve biopsies showed severe neurogenic atrophy and axonal degeneration without inflammation. There was no evidence of primary myopathy. Two patients died of complications of sepsis. Of the survivors, three patients had no further weakness at the time of reexamination, except for peroneal nerve palsy in one patient. Two patients, still in the recovery period, showed markedly improved conditions but still showed slight weakness of the proximal muscles. By electrophysiology, signs of chronic neurogenic damage were demonstrable in all survivors at follow-up. - Conclusions - Critical illness polyneuropathy is a frequent cause of neuromuscular weaning failure in critically ill patients, regardless of the type of primary illness. Involvement of proximal (including facial and paraspinal) muscles is striking. Tendon reflexes are often preserved. Patients with central nervous system injury may likewise develop critical illness polyneuropathy. In these latter patients, tendon reflexes may even be exaggerated. Recovery from critical illness polyneuropathy is usually rapid and clinically complete, although incomplete on electrodiagnostic study. Residual peripheral nerve lesion, generally of the peroneal nerve, is the most frequent feature of incomplete recovery. The need for careful electrophysiologic testing is emphasized to clarify the nature and extent of neuromuscular disturbances in critically ill patients. Failure to recognize the development of neuropathy in these patients may lead to erroneous conclusions about the ability to wean them from the ventilator.
Gesehen am 04.06.2025